An optimal stock level and pricing strategy for perishable products under the VMI system - Janthratip Khamwarut; Huynh, Trung Luong; Manukid Parnichkun; Mongkol Ekpanyapong; Royal Thai Government Fellowship (Pathum Thani : Asian Institute of Technology, 2024)
Vendor-managed inventory (VMI) is an approach used to ensure that perishable items are always available while also improving operational efficiency and compliance with quality standards. In this study, we study a new decision scenario concerning a deteriorating item, focusing on the case of a single vendor and single retailer under VMI system. We develop the mathematical model considering the base stock policy, which will be implemented with a maximum stock level (S), with adjustments made to discount prices based on shelf life to encourage a retailer to buy products. Demand rates are influenced by pricing, assuming that the rate of deterioration for a deteriorating item follows a Weibull distribution and a fully backlogged shortage. To assess the efficacy of the proposed models, we conduct numerical experiments and sensitivity analyses. These analyses aim to evaluate how changes in input variables impact experimental outcomes and shed light on the effects of alterations in input parameters on optimal solutions. Finally, we present the conclusions drawn from our study, along with recommendations for future research.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Industrial and Manufacturing Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2024
Keywords: Inventory control -- Mathematical models; Weibull distribution; Perishable goods -- Inventory control